Travel agencies: From online channel conflict to multi-channel harmony - Salvado, Josefina (2014)
The adoption of Internet as a distribution channel and a privileged e-commerce tool has pressed Travel Agen- cies (TAs) to a latent channel conflict. Our main interest is to understand how the traditional independent travel agencies in Portugal deal with the online channel. We suggest that TAs have to develop an innovative business model based on the online and offline complementary channels, in order to achieve a multi-channel harmony.